2022
DOI: 10.1186/s40793-022-00406-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial communities following 20 years of fertilization and crop rotation practices in the Czech Republic

Abstract: Background Although fertilization and crop rotation practices are commonly used worldwide in agriculture to maximize crop yields, their long-term effect on the structures of soil microorganisms is still poorly understood. This study investigated the long-term impact of fertilization and crop rotation on soil microbial diversity and the microbial community structure in four different locations with three soil types. Since 1996, manure (MF; 330 kg N/ha), sewage sludge (SF; 330 and SF3x; 990 kg N/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Crop rotation was associated with a much larger effect on the fungal community of soil, rhizosphere and root with significant changes in composition observed in all sample types at all sites. Kracmarova et al [ 41 ] also observed a more pronounced effect of long-term crop rotation (potato, winter wheat, and spring barley) on soil fungal communities compared to the bacterial microbiota. Rotations of rice and canola were also determined to result in increased soil microbial diversity, and the keystone taxa identified in these rotations were all fungal genera [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crop rotation was associated with a much larger effect on the fungal community of soil, rhizosphere and root with significant changes in composition observed in all sample types at all sites. Kracmarova et al [ 41 ] also observed a more pronounced effect of long-term crop rotation (potato, winter wheat, and spring barley) on soil fungal communities compared to the bacterial microbiota. Rotations of rice and canola were also determined to result in increased soil microbial diversity, and the keystone taxa identified in these rotations were all fungal genera [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For adjusting local growth conditions, vegetation can change the soil environment by secreting bioactive molecules into the rhizosphere and changing soil conditions for soil microbial communities (Hu et al, 2018). However, the changes in the composition and diversity of soil microbial communities due to the growth of different types of plants on the same cultivated land have been investigated (Kracmarova et al, 2022; Wei, Li, et al, 2020; Wei, Ma, et al, 2020), however, their relationships with environmental factors need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the communities in soils under crop rotation, many studies have indicated distinct β-diversities of soil bacteria and/or fungi between mono- and rotation-cropping 5 , 6 , 8 , 10 , 12 , 14 18 , 20 22 , 24 , 25 , 27 , 33 or among crop rotations with different crops and rotation sequences, places, and/or periods 5 , 10 , 11 , 15 , 18 22 , 24 , 25 , 32 , 33 ; however, the details of soil biota that change with plant growth have not been clarified in a crop-rotation cycle. We showed that the taxonomic variations indicated by β-diversities in the four sample groups were clearly distinguished by crops as well as by fields (Fig.…”
Section: Discussionmentioning
confidence: 99%